Huge on-Current Ferroelectric-Gate Thin Film Transistor with Solution-Processed Indium Tin Oxide Channel - Minh, Do Hong; Trang, Vu Thi Huyen; Trinh, Bui Nguyen Quoc (VNU Journal of Science: Mathematics - Physics, 2014)
Abstract: We have demonstrated ferroelectric-gate thin film transistors (FGTs) using solution-processed indium tin oxide (ITO) film as an oxide-semiconductor channel and Pb 1.2 Zr 0.4 Ti 0.6 O 3 ferroelectric film as a gate insulator on a poly-crystalline 100-nm-STO/SiO 2 /Si substrate or a single-crystalline STO(111) wafer. The FGTs show a clear memory function with an on/off current ratio of more than 10 5 and a memory window of 2 V. It is interesting that even using solution-processed ITO channel, the saturated “on” current in the FGT reached as high as 4.6 mA at operation voltages of 8 V, corresponding to a field-effect mobility of 8.0 cm 2 /Vs, for the case of single-crystalline STO(111) wafer. The large “on” current is mainly due to the huge induced charge of the ferroelectric gate, compensated to the small mobility of the ITO channel.  Keywords: PZT, Thin film transistor (TFT), ferroelectric, ITO, FeRAM.